BURIAL 121 OF THE KELI BURIAL GROUND OF THE 13TH – 14TH CENTURIES (MOUNTAINOUS INGUSHETIA) - Kockarov, Umar Usufovic; Mamaev, Rasid Hamidovic; Naroznyj, Vitalij Evgen'evic; Naroznyj, Evgenij Ivanovic (History, Archeology and Ethnography of the Caucasus, 2021)
The paper introduces the materials of the Burial 121 of the Keli burial ground of the 13th-14th centuries of Mountainous Ingushetia. The information about the burial and its funerary goods with their partial reconstruction set the main task for our study. This include the most complete identification of the ethnocultural origins of the objects under consideration, as well as the zones of influence and the degree of influence of the Golden Horde on the process and dynamics of the formation of the material culture of the population of the highlands of Ingushetia and a range of its weapons under the powerful impact on them of the surrounding territories during the key events of the 13th-14th centuries. The content of the paper will make it possible to judge the specifics of the military equipment of the mountain warrior-archers, armed with a saber with a surviving deer-horn hilt. The use of synchronous analogies suggests that the discovered saber is the product of the craftsmanship of professional blacksmiths and bone carvers, as well as craftsmen for processing leather for wooden scabbards and hunters who obtained the necessary raw materials. The question of the localization of such crafts in the mountains remains unanswered, and the presence of direct analogies to the published items from the warrior’s arsenal in the burials of the nomads of Eastern Europe during the Golden Horde era does not exclude the possibility of an influx of such items from the Golden Horde plain to the highlands of the Eastern Pridaryal territory. Thus, the Golden Horde Tatartup, a part of the Alanian population which took refuge in the mountains at the end of the 1230s, is of special attention regarding the role in such “mediation”. Traces of these migrants, who gradually “dissolved” in the local environment, are well documented in other burial complexes of the Keli burial ground.